2021
DOI: 10.46989/001c.21213
|View full text |Cite
|
Sign up to set email alerts
|

Changes in juvenile sturgeon erythrocytes across age classes reflects evolutionary development

Abstract: Erythrocytes are important for gas transport and exchange in animals and play an important role in maintaining normal functions of the body. The purpose of this study was to observe the changes in erythrocyte morphology during the development of juvenile sturgeon (Acipenser baeri ♀×Acipenser schrenckii ♂ hybrid F1) and to describe the relationship between erythrocyte morphology and development. We compared the erythrocyte morphology of juvenile sturgeon in three developmental stages. The results showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 9 publications
3
5
0
Order By: Relevance
“…However, previous research has established a direct relationship between body size and cell volume in vertebrates, consistent with the negative correlation that we observed (Gregory 2001;Lahnsteiner 2021). Age-related differences have also been investigated, with older individuals having significantly smaller erythrocytes (Nikinmaa 2020;Yang et al 2021). Unfortunately, in those studies, body size changes were considered akin to aging such that it was unclear whether size, age, or some combination of the two was causing these cellular changes.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…However, previous research has established a direct relationship between body size and cell volume in vertebrates, consistent with the negative correlation that we observed (Gregory 2001;Lahnsteiner 2021). Age-related differences have also been investigated, with older individuals having significantly smaller erythrocytes (Nikinmaa 2020;Yang et al 2021). Unfortunately, in those studies, body size changes were considered akin to aging such that it was unclear whether size, age, or some combination of the two was causing these cellular changes.…”
Section: Discussionsupporting
confidence: 91%
“…Total length and wet mass were both weakly correlated with the changes in MNV over time; like the analysis between populations, the MNV decreased as the individuals grew. This complements recent research, which found that older juvenile sturgeon (40-540 days) had smaller and more numerous erythrocytes (Yang et al 2021). Although statistically significant, the magnitude of change in average MNV within this population over time was small (52.9-55.7 fL).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations